Arterial hypertension as a heart failure predictor in patients with chronic glomerulonephritis and intact renal function - N. Yu. Borovkova; N. N. Borovkov; L. Yu. Koroleva; L. A. Biryukova (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To clarify the role of arterial hypertension (AH) as a possible predictor of chronic heart failure (CHF) in patients with chronic glomerulonephritis (CGN) and intact renal function.Material and methods. In total, 136 CGN patients with various AH stages, intact renal function, and early clinical manifestations of CHF were examined. Remodelling of left ventricular (LV) myocardium, as well as systolic and diastolic LV function, was assessed by echocardiography.Results. In CGN patients with intact renal function, AH resulted in CHF, due to changing LV structure and function. In Stage I AH, early CHF symptoms, without LV hypertrophy (LVH), were associated with LV diastolic dysfunction. Stage II AH was characterised by manifested CHF, concentric LVH, intact LV ejection fraction (EF), and LF diastolic dysfunction. Stage III AH was characterised by systolic and diastolic HF, reduced LV EF, and eccentric LVH.Conclusion. AH could be regarded as a CHF predictor in patients with CGN and intact renal function.